1999
DOI: 10.1073/pnas.96.8.4432
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen inhibits acidification in cells independent of the estrogen receptor

Abstract: Tamoxifen has been reported to have numerous physiological effects that are independent of the estrogen receptor, including sensitization of resistant tumor cells to many chemotherapeutic agents. Drug-resistant cells sequester weak base chemotherapeutics in acidic organelles away from their sites of action in the cytosol and nucleus. This work reports that tamoxifen causes redistribution of weak base chemotherapeutics from acidic organelles to the nucleus in drug-resistant cells. Agents that disrupt organelle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 52 publications
5
93
0
3
Order By: Relevance
“…These different effects may explain the process of cell death induced by this anticancer agent in different cell types, including ER-negative breast cancer (Jordan 1990), lung adenocarcinoma (Croxtall et al, 1994), prostate cancer (Bergan et al, 1999), ovarian carcinoma (Trope et al, 2000), virus (Laurence et al, 1990), and bacteria (Luxo et al, 1996), since ATP is required to maintain the cell viability. Moreover, our data in isolated mitochondria are according to the ⌬⌿ depolarization induced by TAM either in neurons (Hoyt et al, 2000) or in normal human mammary epithelial cells (Dietze et al, 2001) and may explain the inhibition of Ca 2ϩ uptake by the cardiac sarcoplasmic recticulum (Kargacin et al, 2000) and the TAM-induced inhibition of acidification in ER-independent cells (Altan et al, 1999). The mitochondrial depolarization induced by TAM may be also important as an early event in the promotion of apoptosis, a critical process for normal tissue homeostasis that may be involved in the cytotoxic ER-independent effects of TAM observed in vivo (Dietze et al, 2001).…”
Section: Fig 5 Effects Of Tam (-) Andmentioning
confidence: 65%
See 1 more Smart Citation
“…These different effects may explain the process of cell death induced by this anticancer agent in different cell types, including ER-negative breast cancer (Jordan 1990), lung adenocarcinoma (Croxtall et al, 1994), prostate cancer (Bergan et al, 1999), ovarian carcinoma (Trope et al, 2000), virus (Laurence et al, 1990), and bacteria (Luxo et al, 1996), since ATP is required to maintain the cell viability. Moreover, our data in isolated mitochondria are according to the ⌬⌿ depolarization induced by TAM either in neurons (Hoyt et al, 2000) or in normal human mammary epithelial cells (Dietze et al, 2001) and may explain the inhibition of Ca 2ϩ uptake by the cardiac sarcoplasmic recticulum (Kargacin et al, 2000) and the TAM-induced inhibition of acidification in ER-independent cells (Altan et al, 1999). The mitochondrial depolarization induced by TAM may be also important as an early event in the promotion of apoptosis, a critical process for normal tissue homeostasis that may be involved in the cytotoxic ER-independent effects of TAM observed in vivo (Dietze et al, 2001).…”
Section: Fig 5 Effects Of Tam (-) Andmentioning
confidence: 65%
“…However, TAM inhibits also the growth of ER-negative breast cancer cells and other cell types that lack ER (Couldwell et al, 1993;Croxtall et al, 1994;Charlier et al, 1995). Actually, TAM has been reported to have several physiological effects that are ER independent, including sensitization of resistant tumor cells to many chemotherapeutic agents (Altan et al, 1999) and several pleiotropic effects both in vivo and in vitro and references therein). Moreover, it has been reported that TAM induces multiple cellular adverse effects, including hemolytic action (Suwalsky et al, 1998;Cruz Silva et al, 2000) and inhibition of mitochondrial permeability transition (Custódio et al, 1998).…”
mentioning
confidence: 99%
“…It is known that estradiol inhibits cell death induced by TAM (88). Moreover, studies have reported numerous pharmacological effects of TAM that are independent of the estrogen receptor such as its ability to inhibit the acidification of lysosomes (89,90) and induce LMP (91). These effects of TAM ultimately lead to the impairment of lysosomal function and reduction of autophagosome clearance and may explain the decrease in autophagosome degradation observed after incubation with this agent (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…the cytosol or nucleus [85]. Therefore, the co-administration of agents liberating the drugs from these compartments was carried out allowing redistribution of the drug to the active sites [86,87]. In this study, it was revealed that treatment of res-MCF7 cells with Dox-loaded origami objects resulted in elevated pH indicating the inhibition of acidification of lysosomal compartments.…”
Section: Dna Origamimentioning
confidence: 93%